2021
DOI: 10.1007/s11239-021-02474-8
|View full text |Cite
|
Sign up to set email alerts
|

Screening for venous thromboembolism in patients with COVID-19

Abstract: Pulmonary thromboembolism and deep venous thrombosis occur frequently in hospitalised patients with COVID-19, the prevalence increases on the intensive care unit (ICU) and is very high in patients on extracorporeal membrane oxygenation (ECMO). We undertook a literature review to assess the usefulness of screening for peripheral venous thrombosis or pulmonary thrombosis in patients admitted with COVID-19. Outside of the ICU setting, D-dimer elevation on presentation or marked increase from baseline should alert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…28 Microvascular thromboses are difficult to evaluate and often impossible to differentiate from other causes of organ dysfunction without autopsies. 29 Consistent with the literature, 20 this research also found that blood hyperlactatemia has been significantly associated with high mortality risk among critically ill Covid-19 patients in Saudi Arabia. A recent systematic literature review explored the possible association between increased blood lactate levels and mortality in Covid-19 patients and compared lactate values between Covid-19 and non-Covid-19 patients.…”
Section: Discussionsupporting
confidence: 87%
“…28 Microvascular thromboses are difficult to evaluate and often impossible to differentiate from other causes of organ dysfunction without autopsies. 29 Consistent with the literature, 20 this research also found that blood hyperlactatemia has been significantly associated with high mortality risk among critically ill Covid-19 patients in Saudi Arabia. A recent systematic literature review explored the possible association between increased blood lactate levels and mortality in Covid-19 patients and compared lactate values between Covid-19 and non-Covid-19 patients.…”
Section: Discussionsupporting
confidence: 87%
“…On one side, clinical features and symptoms of Covid-19 pneumonia and VTE greatly overlap, preventing us from assessing effectively the pre-test probability of VTE in Covid-19 patients [22,23]. On the other, D-dimer, which has a great negative predictive value for VTE in general population [24], is usually elevated in Covid-19 patients even in absence of VTE [8,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with COVID-19 are at increased risk of developing pulmonary embolism (PE) [ 1 4 ]. However, symptoms of COVID-19 and PE overlap, resulting in diagnostic challenges in patients presenting to the emergency department (ED) [ 5 , 6 ]. CT pulmonary angiography (CTPA) is considered the gold standard for PE, but performing this test in all COVID-19 patients would be logistically challenging, and lead to considerable costs and unnecessary exposure to radiation and contrast agents.…”
Section: Introductionmentioning
confidence: 99%